Tuning Hyrbrid Ferroelectric and Antiferroelectric Stacks for Low Power FeFET and FeRAM Applications by Using Laminated HSO and HZO films. (5th January 2022) - Ali, Tarek; Lehninger, David; Lederer, Maximilian; Li, Songrui; Kühnel, Kati; Mart, Clemens; Mertens, Konstantin; Hoffmann, Raik; Olivo, Ricardo; Emara, Jennifer; Biedermann, Kati; Metzger, Joachim; et al.
Abstract: The properties of hybrid ferroelectric (FE) and antiFE (AFE) films integrated in a single capacitor stack is reported. The stack lamination (4 × 5 nm) or (2 × 10 nm) using an Alumina (Al2 O3 ) interlayer, material type (Si‐doped HfO2 (HSO) and Zr doped HfO2 (HZO)), precursor condition (TEMA‐Hf and Hf/ZrCl4 ), or dopant concentration (Si and Zr) are investigated for laminate stack properties. Optimized FE properties (higher 2 P r and a lower fraction of the monoclinic phase) are observed at (2 × 10 nm) laminates compared to a single 20 nm film thickness. The hybrid laminate stack as FE‐FE, AFE‐FE, DE‐FE, or DE‐AFE using (2 × 10 nm) based laminates are explored in terms of the output FE hysteresis (2 P r, 2 E c ) and structural properties by X‐ray diffraction. The hybrid AFE‐FE stack shows the potential of tailoring the output FE hysteresis 2 E c by varying the fraction of the AFE phase. The hybrid AFE‐FE stack is studied for the HSO and HZO materials at optimal FE content for the first laminate layer while varying the Si or Zr content to stabilize different degrees of an AFE phase in the second laminate layer. The superposition of the hybrid AFE‐FE hysteresis shows a systematic 2 E c control. A model is developed to describe the tailored output FE hysteresis via the tuning of a hybrid AFE‐FE stack. The role of stack lamination at hybrid‐stabilized phases inside a single stack is explored with the aim for a controlled and optimized FE hysteresis shape toward a low power (2 E c ) operation. Abstract : The properties of hybrid ferroelectric (FE) and antiferroelectric (AFE) films integrated in a single capacitor stack is reported. The hybrid laminate stack as FE‐FE, AFE‐FE, dielectric (DE)‐FE, or DE‐AFE using (2 × 10 nm) based laminates are explored in terms of the output FE hysteresis (2 P r, 2 E c ) and structural properties by X‐ray diffraction. The hybrid AFE‐FE stack shows the potential of tailoring the output FE hysteresis 2 E c by varying the fraction of the AFE phase.